TRACKING MAP UNTUK MONITORING GANGGUAN JTR PADA NH FUSE GARDU DISTRIBUSI - Kiswantono, Agus (Universitas Lampung, 2025)
This research develops an IoT-based fault monitoring system for Low Voltage (LV) Networks using a tracking map on NH fuses, aiming to improve response time efficiency and fault detection accuracy. The system integrates sensors with a web-based platform to monitor and visualize fault locations in real-time. Test results indicate that the system is capable of detecting faults with high accuracy, with detection errors as low as 0% to 0.32%. The response time for fault detection ranges from 0.5 to 1 second, significantly faster than conventional methods. As a result, fault recovery time can be accelerated by 30-40%, potentially enhancing the reliability of the power supply. Additionally, the use of IoT technology allows more efficient monitoring and quicker response to faults, enabling faster repair processes and minimizing downtime. Although the system demonstrates promising results, the study also identifies areas for further development, particularly in integrating it with more complex distribution management systems and enhancing data analytics. Overall, the proposed system offers an innovative solution for mitigating faults in LV networks, improving reliability, and increasing operational efficiency in power distribution systems